A decision‐making support model for enterprises localization strategies. Issue 1 (2014) - Marzia Morena; Maria Luisa Del Gatto; Anna Gornati
<x xml:space="preserve"> Abstract </x> Purpose – The paper aims at describing a supporting model for the decision‐making process that may steer the location decisions of international businesses. This is made possible by a measurement system where the characteristics of a territory are assessed with reference to some key factors that are internationally known to investors, to the aim of spotting the best location to implement a property investment. Design/methodology/approach – The surveys analysed when producing this paper highlighted the presence of internationally renowned and shared factors that the enterprises generally take into consideration in their decision‐making process, and which strongly influence the decision to locate a business in a territory to the detriment of another. By adopting and organizing these "key factors" in a systemic way, the model introduced in this paper supports enterprises in their location choice. It analyses and measures some territorial contexts (with no limits regarding their size) based on the scores assigned to these contexts after the analysis of the 12 key factors. Findings – The analysis had two outputs: on the one hand, its results allowed to check whether the areas are actually in line with the expectations and with the requirements of a potential investor, with reference to the activity that such investor is willing to promote; on the other, the identification of the characteristics of the area provides the basis to define the vocation of the areas under examination, thus helping the drawing of future development scenarios. Originality/value – The surveys analysed when producing this paper highlighted the presence of internationally renowned and shared factors that the enterprises generally take into consideration in their decision‐making process, and which strongly influence the decision to locate a business in a territory to the detriment of another.